Angry populists or concerned citizens? How linguistic emotion ascriptions shape affective, cognitive, and behavioural responses to political outgroups. Issue 1 (2nd January 2023) - Wunderlich, Philipp; Nguyen, Christoph; von Scheve, Christian
ABSTRACT: Emotion expressions of outgroup members inform judgements and prompt affective responses in observers, shaping intergroup relations. However, in the context of political group conflicts, emotions are not always directly observed in face-to-face interactions. Instead, they are frequently linguistically ascribed to particular actors or groups. Examples of such emotion ascriptions are found, among others, in media reports and political campaign messaging. For instance, anger and fear are frequently evoked in connection with and ascribed to right-wing populist groups. Yet not much is known about the specific effects that ascriptions of discrete emotions to outgroups can have on intergroup relations. With this pre-registered study, we contribute to bridging this gap by analysing the effects of ascriptions of anger and fear to a right-wing populist outgroup. In an online survey experiment, administered to a sample of the German general population ( N  = 3500), we manipulated the emotions ascribed to these outgroups using brief vignettes. Our findings suggest that ascriptions of anger to right-wing populist outgroups increase reactive anger in observers, whereas ascriptions of fear reduce anger as well as contempt towards populists. Effects of ascribed emotions on stereotype content and action tendencies could not be identified.